Serositis as an indicator of poor prognosis in pediatric systemic lupus erythematosus - Wei-Chen Kao; Ya-Chiao Hu; Jyh-Hong Lee; Li-Chieh Wang; Yu-Tsan Lin; Yao-Hsu Yang; Bor-Luen Chiang; Hsin-Hui Yu (Pediatric Rheumatology Online Journal, 2025)
Abstract Background Systemic lupus erythematosus (SLE) is a multi-systemic autoimmune disease that causes inflammation of the serosa (serositis). This retrospective study aimed to evaluate the clinical characteristics of serositis in childhood-onset SLE (cSLE) and analyze its association with long-term outcomes. Methods We retrospectively reviewed the medical records of patients with cSLE diagnosed at a medical center in Taiwan, analyzing data collected from January 2002 to December 2022. We analyzed the clinical features of patients with serositis as pleuritis and/or pericarditis with at least a small effusion (> 0.5 cm in depth) on sonography or chest radiography. Cox proportional hazards regression was used to calculate the hazard ratios (HR) and 95% confidence intervals (CI) for the association between serositis and all-cause mortality. Results 185 patients with cSLE were enrolled, of whom 38 (20.54%) had serositis. Patients with serositis had a younger age at SLE diagnosis, a higher SLE Disease Activity Index 2000 score at serositis diagnosis, and an increased prevalence of lupus nephritis, central nervous system manifestations, end-stage renal disease (ESRD), a higher Systemic Lupus International Collaborating Clinics (SLICC)/American College of Rheumatology (ACR) damage index score, and a higher mortality than that of patients without serositis. Multivariate Cox regression analysis showed that both serositis (hazard ratio [HR]: 5.585, confidence interval [CI]: 1.853–17.80) and ESRD (HR: 13.956; CI: 3.822–50.964) were associated with mortality risk. Kaplan–Meier survival curve analysis revealed that patients with both serositis and ESRD had the poorest 20-year survival rate. Patients with late-onset serositis (occurring 1 year after SLE diagnosis) had higher mortality rates than those with early-onset serositis. Conclusion Children with lupus serositis had higher disease activity, a higher prevalence of comorbidities, and mortality. Patients with both serositis, especially late-onset serositis, and ESRD had an increased risk of poor long-term survival.